The recognition of pathogens by C-type lectins - Brown, Gordon D. (Henry Stewart Talks, 2012)
Role of pattern recognition receptors in extracellular pathogen recognition, TLR and CLR, Soluble CLRs and opsonisation, MBL, SPA, SPD, Membrane CLRs and signal transduction, Mannose Receptor, DC-SIGN, Dectin-1, Dectin-2, MINCLE, Innate and adaptive immune responses